Patients with Postpartum Depression in Gynaecological Practices in Germany – Results of a Representative Survey of Local Gynaecologists about Diagnosis and Management - Pawils, S.; Metzner, F.; Wendt, C.; Raus, S.; Shedden-Mora, M.; Wlodarczyk, O.; Härter, M. (Geburtshilfe und Frauenheilkunde, 2016)
Theoretical Background and Current Issues: For the sake of pre-emptive child protection it is necessary to recognise signs of postpartum depression (PPD) in pregnant women and young mothers as early as possible and to initiate adequate assistance. Because of their high acceptance, especially in the phases of pregnancy and birth, the local gynaecologists offer ideal prerequisites for access to the parents. This study evaluates the current status of diagnosis and management of PPD in gynaecological practices. Material and Methods: In a representative German nation-wide questionnaire survey taking the regional distribution into account n = 3000 local gynaecologists were selected at random and contacted by post. The questionnaire addressed their approaches to the diagnosis and management of PPD as well as the encountered barriers. Results: Among the n = 1034 participating gynaecologists (response rate: 35 %) half of them dealt actively with PPD; 16 % used a questionnaire for this purpose. Consultation by the gynaecologist (84 %) or referral to therapists or hospitals (86 %) were among the most common interventions in the management of PPD. A need for improvement in the management of women with PPD was recognised equally often. As barriers the gynaecologists mentioned above all the lack of time, the low reimbursements for consultations and the lack of effective treatment options. Predictors for an active anamnesis were found to be female gender of the gynaecologist, possession of an additional psychosomatic qualification and practice located in an urban catchment area or state of the former West Germany. Conclusion: The results clearly demonstrate a high acceptance for the management of PPD by gynaecologists as well as the need for further action to improve the care of patients with PPD in gynaecological practices.
Keywords: postpartum depression; gynaecologists; pregnancy; screening; representative survey